2006
DOI: 10.1002/dvdy.20888
|View full text |Cite
|
Sign up to set email alerts
|

Selective assembly of fibulin‐1 splice variants reveals distinct extracellular matrix networks and novel functions for perlecan/UNC‐52 splice variants

Abstract: Fibulin-1C and fibulin-1D splice variants have been conserved throughout metazoan evolution and have distinct functions in Caenorhabditis elegans development. Both splice variants are required for the assembly of hemidesmosome-mediated mechanosensory neuron and uterine attachments, although the molecular associations that underlie their distinct functions at these locations are not known. Here, we show that the assembly of fibulin-1C and fibulin-1D splice variants at these anchorages is dependent upon distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Eumetazoans possess a complex embryonary development that gives rise to differentiated tissue layers and which is dependent on the presence of a complex ECM that serves as the medium for cell migration, cell-cell communication, and reservoir of growth factor substances (Morris, 1993). A Eumetazoan origin is supported by the roles of FBLNs in protostomes like C. elegans, where they associate with the basement membrane and regulate cell adhesion processes (Hesselson et al, 2004;Kubota et al, 2004;Muriel et al, 2006;Vogel et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Eumetazoans possess a complex embryonary development that gives rise to differentiated tissue layers and which is dependent on the presence of a complex ECM that serves as the medium for cell migration, cell-cell communication, and reservoir of growth factor substances (Morris, 1993). A Eumetazoan origin is supported by the roles of FBLNs in protostomes like C. elegans, where they associate with the basement membrane and regulate cell adhesion processes (Hesselson et al, 2004;Kubota et al, 2004;Muriel et al, 2006;Vogel et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Fibulin-1D assembles in the flexible polymers that connect the pharynx and body wall muscle. Both isoforms requires fibulin-6 (hemicentin) for assembly at hemidesmosomes-mediated mechanosensory neuron and uterine attachments to the epidermis [90]. In addition, assembly of fibulin-1C at uterine and mechanosensory neuron attachments is depend on perlecan, whereas assembly of fibulin-1D at mechanosensory neuron attachments is dependent on laminin [90].…”
Section: Fibulin Animal Modelsmentioning
confidence: 99%
“…S4) different from EV. Fibulin binds to laminins and nidogens of the BM (Kramer 2005) and the assembly of fbl-1 at mechanosensory neuron attachments is dependent on epi-1 (Muriel et al 2006) , which may explain the observed effect on paralysis. Similarly, dystroglycan is a receptor for epi-1 (Johnson et al 2006).…”
Section: Resultsmentioning
confidence: 99%